2008
DOI: 10.1007/s11064-008-9717-6
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of HCN Channels and Their Participation in Neuropathic Pain

Abstract: Neuropathic pain is induced by the injury to nervous systems and characterized by hyperalgesia, allodynia and spontaneous pain. The underlying mechanisms include peripheral and central sensitization resulted from neuronal hyperexcitability. A number of ion channels are considered to contribute to the neuronal hyperexcitability. Here, we particularly concentrate on an interesting ion channel, hyperpolarization-activated cyclic nucleotide gated (HCN) channels. We overview its biophysical properties, physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 101 publications
(153 reference statements)
5
39
0
Order By: Relevance
“…Whilst the former are rapid and reversible modes of channel modulation, transcriptional regulation can persist over a longer period. Indeed, transcriptional changes in HCN expression have been reported to accompany neuronal development and maturation as well as the onset of abnormal electrical activity such as occurs in epilepsy or following nerve injury Brewster et al, 2002;Frere et al, 2004;Jiang et al, 2008;Richichi et al, 2008;Santoro et al, 2004). The results presented here hint that a similar transcriptional mechanism is at play with administration of BDNF and NT3 at 10 ng/ml given that I h amplitude was significantly larger but was not accompanied by a shift in kinetics or significant change in voltage-dependence.…”
Section: Hyperpolarization-activated Currents Increase In the Presencsupporting
confidence: 53%
“…Whilst the former are rapid and reversible modes of channel modulation, transcriptional regulation can persist over a longer period. Indeed, transcriptional changes in HCN expression have been reported to accompany neuronal development and maturation as well as the onset of abnormal electrical activity such as occurs in epilepsy or following nerve injury Brewster et al, 2002;Frere et al, 2004;Jiang et al, 2008;Richichi et al, 2008;Santoro et al, 2004). The results presented here hint that a similar transcriptional mechanism is at play with administration of BDNF and NT3 at 10 ng/ml given that I h amplitude was significantly larger but was not accompanied by a shift in kinetics or significant change in voltage-dependence.…”
Section: Hyperpolarization-activated Currents Increase In the Presencsupporting
confidence: 53%
“…In our present investigation, ZD7288 was used in a concentration range of 0.1 to 30 uM. This concentration range was commonly used for blocking HCN currents [1,2,12,17]. Therefore, the ZD7288 concentrations that were used in the present study were not in the high concentration range that was found to affect other channels non-specifically.…”
Section: Discussionmentioning
confidence: 99%
“…current termed I f , I q , or I h [see reviews (Kaupp and Seifert 2001;Robinson and Siegelbaum 2003)]. Deviations in HCN expression or function can contribute to several disease states (Benarroch 2013), including cardiac arrhythmias (Stieber et al 2004), epilepsy (Noam et al 2011) and neuropathic pain (Jiang et al 2008). There are four mammalian genes encoding HCN subtypes (HCN1-HCN4), and in vivo HCN channels typically include at least two subtypes.…”
Section: Introductionmentioning
confidence: 99%